Corporate Social Responsibility as Work Law: A Critical Assessment in the Light of the Principle of Human Dignity Workplace Pensions: Next Generation or Final Frontier - Martin, Isabelle (Canadian Labour and Employment Law Journal, 2015)
The organization of work through production networks undermines the application of labour law to a growing proportion of workers. Protections put in place by labour law, specifically devised to apply within the hierarchical and bilateral structure of the employer/employee relationship, are ill-fitted to tackle the multilateral structure of network production in which market and hierarchical relationships are entangled. Corporate social responsibility (CSR) appears to some as a possible answer to these challenges. The author develops a normative and functional framework to assess the promise and limits of CSR as a regulatory tool. The framework is grounded in human dignity, as concep- tualized by human rights law and political philosophy. A holistic understanding of human dignity highlights the interdependency of labour law's basic func- tions: providing minimum working conditions, ensuring employer accountability for working hazards, and enabling workers' collective action. The author then applies the human dignity framework to codes of conduct, as described and analyzed in current literature on the subject. She concludes that CSR codes and their implementation often fall short of what is required in the workplace by the human dignity principle.